Cardiovascular protein profiling in patients with first-episode psychosis - Anna Malmqvist; Feride Eren; Lilly Schwieler; Funda Orhan; Helena Fatouros-Bergman; Lena Flyckt; Fredrik Piehl; Simon Cervenka; Magnus Bäck; Carl M. Sellgren; Göran Engberg; Sophie Erhardt (Schizophrenia)
Abstract Patients with schizophrenia have a threefold higher mortality from cardiovascular disease than people in the general population. Atherosclerosis is linked to immune activation, a process tentatively entwined with the underlying pathophysiological mechanisms of schizophrenia. The aim of the present study was to investigate an extensive array of cardiovascular biomarkers in individuals experiencing their first episode of psychosis (FEP), either drug-naïve or exposed to short-term antipsychotic treatment, alongside a group of healthy controls (HC). Using the OLINK Proximity Extension Assay, Cardiovascular II Panel, we analyzed plasma from 72 FEP patients, including 42 later diagnosed with schizophrenia and 54 HCs. Biomarker levels, that significantly differed between patients and controls, were correlated with symptom severity, cognitive performance and cardiovascular risk factors. Fifteen out of 92 cardiovascular biomarkers were higher in individuals with FEP compared to HC, and one biomarker was lower in FEP patients compared to HC. BMI, waist size, blood pressure, fp-glucose, HbA1c and serum lipid levels were similar between the groups. No correlations that held for multiple comparisons were seen between biomarker concentrations and symptom severity, cognitive performance or cardiovascular risk factors in FEP patients. Higher concentrations of several cardiovascular biomarkers were observed in individuals with FEP compared to in HC. This suggests that patients with FEP are at an increased risk of developing cardiovascular disease from the onset of psychosis, even before changes in traditional biomarkers are detectable. It underscores the need for innovative approaches to detect and monitor this risk early.